(1S)-(−)-N-Trifluoromethylthio-2, 10-camphorsultam and its derivatives: easily available, optically pure reagents for asymmetric trifluoromethylthiolation. Issue 6 (22nd February 2017) - Zhang, He; Leng, Xuebing; Wan, Xiaolong; Shen, Qilong
Abstract : Optically pure reagents that are able to deliver a trifluoromethylthio group with good to excellent enantioselectivities. Abstract : A family of easily scalable, shelf-stable, optically pure reagents (1 S )-(−)- N -trifluoromethylthio-2, 10-camphorsultam1a–c was successfully developed. In particular, compound1c was shown to be an efficient reagent that is capable of transferring chirality to other prochiral nucleophiles such as β-ketoesters, oxindoles and benzofuranones with good to excellent enantioselectivities.